Identification and distribution of Meloidogyne spp. in tomato in Sinaloa Mexico - Martínez Gallardo, José Ángel; Valdés, Tomás Díaz; Molar, Raúl Allende; Manjarrez, Jesús Enrique Retes; Carrillo Fasio, José Armando (Revista Mexicana de Ciencias Agrícolas, 2019)
Worldwide, the most important phytoparasitic nematode genus is Meloidogyne, since it affects more than 3 000 plant species and its infection is characterized by the formation of galls in the root of the infected plant. In Sinaloa, the current distribution of Meloidogyne is unknown, because the most recent reports are from the year 2000 and 2001, identifying the species M. incognita, M. arenaria, M. hapla and M. javanica, distributed in the state. In the present work of investigation, the objectives were to identify morphologically and molecularly the species of the root-knot nematode (Meloidogyne spp.), as well as, to determine its distribution in the culture of tomato (Solanum lycopersicum L), in Sinaloa, Mexico. Cultivated lots with tomato were sampled in the different horticultural zones of Sinaloa, Mexico, during the agricultural cycles 2013-2014, 2014-2015, 2015-2016 and 2016-2017, in the open field, shade mesh and greenhouses, where samples of soil and roots, to perform morphological and molecular identification. The species identified in the samples collected were M. enterolobii, M. incognita and M. arenaria with 88, 10 and 2% incidence respectively. These results indicate that M. enterolobii, M. incognita and M. arenaria are distributed in the state of Sinaloa in the tomato crop, being M. enterolobii the predominant species.